Full-Wave Simulation of Body Absorption due to Radiated Fields at GHz Frequencies - Jose Alberto Carballo-Madrigal; Renato Rimolo-Donadio; Christian Schuster (Tecnología en Marcha)
Exposition of humans to non-ionizing radiation at high frequencies has become ubiquitous due to the higher number of systems operating in that frequency range such as cell phones, wireless networks, and communication systems. The modeling of the impact of this type of radiation is an important issue due to potential short and long-term health effects and for the establishment of regulatory safety limits. From the simulation point of view, this is a challenging task since the wavelengths of interest are much smaller than the typical dimensions of a human body, which leads to the requirement of very fine discretization of the geometrical models and the consequent high demand of computational resources and long execution times.